A Four-Valued Logical Framework for Reasoning About Fiction - Peron, Newton; Antunes, Henrique (Logic and Logical Philosophy, 2022)
In view of the limitations of classical, free, and modal logics to deal with fictional names, we develop in this paper a four-valued logical framework that we see as a promising strategy for modeling contexts of reasoning in which those names occur. Specifically, we propose to evaluate statements in terms of factual and fictional truth values in such a way that, say, declaring ‘Socrates is a man’ to be true does not come down to the same thing as declaring ‘Sherlock Holmes is a man’ to be so. As a result, our framework is capable of representing reasoning involving fictional characters that avoids evaluating statements according to the same semantic standards. The framework encompasses two logics that differ according to alternative ways one may interpret the relationships among the factual and fictional truth values.